Measuring and explaining competition in the financial sector - Jacob A. Bikker; Laura Spierdijk (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2009)
The first part of this paper provides a systematic discussion of the structural problems of competition on financial markets as observed from the demand and from the supply side, using a diagnostic framework. Potential impediments to competition are concentration, entry barriers, lack of transparency, product complexity, switching and search costs, financial illiteracy, lack of consumer power and weak intermediaries. In response to such financial market failures, we suggest a number of possible policy reactions. The second part of the paper investigates ways to measure competition and provides empirical figures on banking competition in 101 separate countries and assesses the market structure as monopolistic (or a perfect cartel), perfectly competitive or monopolistic competitive. Also, banking competition is explained, using explanatory variables of market structure, contestability, inter-industry competition, and institutional and macro economic conditions. This analysis provides possible instruments for reform in order to help promote competition. Next, the impact of banking consolidation is examined. Finally, developments in competition are observed over time, generally pointing to a downward trend.
Keywords: 330; competition; concentration; entry barriers; transparency; consolidation; contestability; institutional conditions; restrictions on activities or investment; regulation; Panzar-Rosse model